Simultaneous Estimation of Levofloxacin Hemihydrate and Ornidazole in Tablet Dosage Form by HPTLC - SURENDRA, K.; MAGESWARI, S.D.; MAHESWARI, R.; HARIKRISHNAN, N.; ROOSEWELT, C.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A validated HPTLC method for simultaneous estimation of levofloxacin hemihydrate and ornidazole in tablet formulations is described. Separation was achieved on precoated silica gel plate 60 F254 using n-butanol:water:glaceal acetic acid (60:20:20) as mobile phase. Quantitation was carried out by the use of densitometer in absorbance mode at 366 nm. Linearity of detector response for levofloxacin hemihydrate and ornidazole estimated in the average weight of the tablet were found to be 99.7 and 100.45 %, respectively. The proposed method is accurate, precise and reproducible and can be adopted for routine analysis of levofloxacin hemihydrate and ornidazole in tablet formulation.